Endovascular treatment of an aneurysm associated with fenestration of the supraclinoid internal carotid artery: Case report and review of the literature - Filep, Rareṣ Cristian; Constantin, Cristian; Arbǎnaṣi, Emil Marian; Mureṣan, Adrian Vasile; Russu, Eliza; Mǎrginean, Lucian (Frontiers in Neurology, 2022)
Background Fenestrations or divisions of the vascular lumen into separate channels appear to be common anatomical variations in patients with intracranial aneurysms. The most frequent sites of occurrence are the anterior communicating artery (ACom), followed by vertebrobasilar and middle cerebral artery (MCA) locations. Case presentation A 61-year-old female was brought to the emergency department after experiencing severe headache with abrupt onset, nausea, and vomiting. Clinical examination on arrival showed a drowsy patient (GCS 14), with neck stiffness, but no cranial nerve palsies or other neurological deficits (Hunt-Hess 2). Non-contrast head CT and CT angiography revealed subarachnoid and intraventricular hemorrhage (modified Fisher 4) and two saccular aneurysms, one located on the right supraclinoid ICA with peripheral calcifications, measuring 20 × 12 mm, the second on the left MCA bifurcation, 6 × 4 mm. 3D rotational angiography revealed a right ICA fenestration located between the ophthalmic (OA) and posterior communicating artery (PCom). The proximal part of the fenestration harbored a large saccular aneurysm projecting superiorly with the neck engulfing the origin of the fenestration; due to the favorable neck and geometry of the aneurysm, endovascular coil occlusion was chosen as a treatment option without balloon or stent assistance. The decision was taken to clip the MCA aneurysm. Conclusion Supraclinoid ICA fenestrations are rare anatomical variations. Endovascular treatment of supraclinoid ICA fenestration-related aneurysms is feasible and safe, with the notable concern of perforators originating from the limbs.